2018
DOI: 10.1038/s41598-018-36055-2
|View full text |Cite
|
Sign up to set email alerts
|

A gB/CD3 bispecific BiTE antibody construct for targeting Human Cytomegalovirus-infected cells

Abstract: Bispecific T cell engager (BiTE) antibody constructs are successfully used as cancer therapeutics. We hypothesized that this treatment strategy could also be applicable for therapy of human cytomegalovirus (HCMV) infection, since HCMV-encoded proteins are abundantly expressed on the surface of infected cells. Here we show that a BiTE antibody construct directed against HCMV glycoprotein B (gB) and CD3 efficiently triggers T cells to secrete IFN-γ and TNF upon co-culture with fibroblasts infected with HCMV stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 57 publications
0
15
0
Order By: Relevance
“…Bispecific T cell engagers (Bites) are already approved for use in humans, following the accelerated approval of Blinatumomab (CD19-CD3 Bite) in March 2018 for B-cell lymphomas (Kantarjian et al, 2017). Other studies also showed that Bites could be employed against Her2 (Yu et al, 2019), BCMA (Goldstein et al, 2020), EpCAM (Ferrari et al, 2015), EGFR (Lutterbuese et al, 2010), CD20 (Hosseini et al, 2020), and PDL1 (Horn et al, 2017) expressing cancers; and diseased cells infected by CMV (Brey et al, 2018) and HIV (Sung et al, 2015). Compared to current treatments (such as neutralizing antibodies or anti-virals) ACE2-Bite approach may potentially be effective both at early stages (as neutralizer of the virus entry) and later stages of the infection when antibody immune defenses are breached, and T cells become more important in restricting the spread of the virus in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bispecific T cell engagers (Bites) are already approved for use in humans, following the accelerated approval of Blinatumomab (CD19-CD3 Bite) in March 2018 for B-cell lymphomas (Kantarjian et al, 2017). Other studies also showed that Bites could be employed against Her2 (Yu et al, 2019), BCMA (Goldstein et al, 2020), EpCAM (Ferrari et al, 2015), EGFR (Lutterbuese et al, 2010), CD20 (Hosseini et al, 2020), and PDL1 (Horn et al, 2017) expressing cancers; and diseased cells infected by CMV (Brey et al, 2018) and HIV (Sung et al, 2015). Compared to current treatments (such as neutralizing antibodies or anti-virals) ACE2-Bite approach may potentially be effective both at early stages (as neutralizer of the virus entry) and later stages of the infection when antibody immune defenses are breached, and T cells become more important in restricting the spread of the virus in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a B cell surface protein (CD19) specific Bite called Blinatumomab (CD19-CD3 Bite) have already been approved to be used in B cell lymphoma patients in 2018 (35). Other studies also showed that Bites could be employed against Her2 (36), BCMA (37), EpCAM (38), EGFR (39), CD20 (40), and PDL1 (41) expressing cancers; and diseased cells infected by CMV (42) and HIV (43). Compared to current treatments (such as neutralizing antibodies or anti-virals) ACE2-Bite approach may potentially be effective both at early stages (as neutralizer of the virus entry) and later stages of the infection when antibody immune defenses are breached, and T cells become more important in restricting the spread of the virus in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…To combine the high potency of the pentamer-specific antibody and broad cell-type coverage of the gB-specific antibody, we developed a bispecific neutralizing antibody based on MAbs 3-25 and 2-18. Recently, our group and another group have reported the development of anti-CD3/anti-gB-based bispecific T-cell engagers (BiTEs) that redirect cytotoxic T cells for killing of HCMV-infected cells ( 48 , 49 ). While the anti-gB/CD3-bispecific antibodies aim to eradicate virus-infected cells, our bispecific antibody has the potential to neutralize circulating free virus and inhibit cell-to-cell viral spreading.…”
Section: Discussionmentioning
confidence: 99%
“…We previously characterized a gB AD-2-specific broadly neutralizing MAb, 3-25, and a pentamer-specific potently neutralizing MAb, 2-18 (33,35). To combine the high potency of the pentamer-specific antibody and broad cell-type coverage of the gB-specific antibody, we developed a bispecific neutralizing antibody based on engagers (BiTEs) that redirect cytotoxic T cells for killing of HCMV-infected cells (48,49). While the anti-gB/CD3-bispecific antibodies aim to eradicate virus-infected cells, our bispecific antibody has the potential to neutralize circulating free virus and inhibit cell-to-cell viral spreading.…”
Section: Discussionmentioning
confidence: 99%
“…CAR T cells targeting gB or other HCMV glycoproteins showed specific cytokine secretion and lysis of target cells in vitro , albeit with only weak efficacy ( 82 83 ). In a later study, Brey et al used bispecific antibodies targeting gB and CD3 and showed that although the T cells still had poor cytotoxic function, likely influenced by HCMV-encoded UL36 and UL37x1 which inhibit apoptosis, the cytokines secreted by the T cells halted viral replication ( 84 ). Further studies are required to assess their effectiveness in vivo .…”
Section: Car T Cells Beyond Oncologymentioning
confidence: 99%